Physicochemical Characterization And Antioxidant Activity Of Petai Pod (Parkia Speciosa) As Agrowaste Fibrous Materials And Residues - Ali, Ahmad FIkri; Shakila Abdullah (Enhanced Knowledge in Sciences and Technology, 2024)
This study explores the physicochemical and antioxidant properties of Parkia speciosa pod extract, focusing on the impact of different processing techniques. The purpose of this study is to evaluate the potential of raw P. speciosa pods for the production of useful fibres with a focus on minimal processing. Among the goals are to describe the fibrous material and residue physicochemical and antioxidant characteristics. The work included acquiring P. speciosa from the local market, processing the pods, and performing assays for TPC, total flavonoid content, DPPH, ABTS, and FRAP. Physicochemical analysis in this study is colour, pH, functional groups, and water solubility assessments. Additionally, the antimicrobial activity against E. Coli and B. cereus was assessed. P. speciosa pods were gathered and prepared, bioactive components are extracted using methanol, and proximate analyses for moisture, protein, and ash content are carried out as part of the study. Proximate analysis for petai pod displayed a moisture content of 16.18%, ash content of 0.05%, and a protein content of 10.84%. Physicochemical analysis revealed a pH of 6.04, a light greenish-yellow color, and 31.39% water solubility. Antioxidant analysis indicated a substantial total phenolic content (TPC), Total Flavanoid content, DPPH and ABTS with result 1.25 mg GAE/g, 3.23 mg GAE/g, 25..87% and 62.87% showcasing significant antioxidant properties. The study underscores the potential of P. speciosa pods as a plant-based protein source and dietary alternative, emphasizing the impact of processing techniques on extract composition and performance. These findings contribute valuable insights for industries seeking diverse and sustainable protein sources. By investigating the byproducts of the petai plant and focusing on antioxidants, proximate analysis, antibacterial activity, and physicochemical qualities, this study unlocks the plant’s potential. Innovations in medicinal uses, nutraceuticals, and functional foods may result from a better understanding of its chemical makeup. The study also looks at its potential as an antibacterial or natural preservative, which offers a variety of industry-specific uses.